Characteristics and circumstances of injuries vary with ethnicity of different population groups living in the same country. Issue 1 (2nd January 2017) - Tiruneh, Abebe; Siman-Tov, Maya; Radomislensky, Irina; ITG,; Peleg, Kobi
ABSTRACT: Objective. To examine whether characteristics and circumstances of injuries are related to ethnicity. Design. The study was based on the Israeli National Trauma Registry data for patients hospitalized between 2008 and 2011. Data included demographics, injury, hospital resource utilization characteristics and outcome at discharge. Univariate analysis followed by logistic regression models were undertaken to examine the relationship between injury and ethnicity. Results. The study included 116, 946 subjects; 1% were Ethiopian Born Israelis (EBI), 11% Israelis born in the Former Soviet Union (FSUBI) and 88% the remaining Israelis (RI). EBI were injured more on street or at work place and had higher rates of penetrating and severe injuries. However, FSUBI were mostly injured at home, and had higher rates of fall injuries and hip fracture. Adjusted analysis showed that EBI and FSUBI were more likely to be hospitalized because of violence-related injuries compared with RI but less likely because of road traffic injuries. Undergoing surgery and referral for rehabilitation were greater among FSUBI, while admission to intensive care unit was greater among EBI. Conclusion. Targeted intervention programmes need to be developed for immigrants of different countries of origin in accordance with the identified characteristics.